The Intensity Attack of Leaf Pest Graphium agamemnon L. and Its Parasitoid Potency on Monoculture and Agroforestry Manglid (Magnolia champaca) Patterns - Endah Suhaendah; Aji Winara (Balai Penerapan Standar Instrumen Lingkungan Hidup dan Kehutanan (BPPLHK)Manado, 2018)
The purpose of this research is to compare the intensity attack of G. agamemnon on monoculture and manglid agroforestry patterns, to identify G. agamemnon parasitoid and to compare the level of parasitization on monoculture and manglid agroforestry patterns. The method used is direct observation of manglid with parameters such as G. agamemnon intensity attack on monocultur and agroforestry, morphology identification of parasitoid type and parasitization level on monoculture and agroforestry. The results showed that G. agamemnon attack on monoculture pattern reached 39.25 % and 25.75 % on agroforestry pattern. The type of parasitoid that attacks G. agamemnon larvae is Diaparsis sp. Parasitization of Diaparsis sp. on monoculture and agroforestry manglid pattern were 55.00 % and 66.67%. Keywords: Diaparsis, Graphium, manglid, parasitoid, pest.